Estudo das biomoléculas presentes nos alimentos: uma possibilidade para a aprendizagem das funções orgânicas - Vieira, Vilma Ferreira de Bello (Universidade Federal de São Carlos, 2023)
STUDY OF BIOMOLECULES IN FOOD: A POSSIBILITY FOR LEARNING ORGANIC FUNCTIONS. Throughout my experience in the classroom, it has been a great challenge to teach organic functions to students of the Technical Course in Pharmacy. Because they do not understand the meaning of Chemistry in their lives, students feel discouraged with traditional teaching that does not give meaning to what is being taught to them. This project was applied in the first half of 2022, to one class of the 1st module of Technical Education in Pharmacy at ETEC Francisco Garcia, located in the city of Mococa/SP, part of the State Center of Technological Education Paula Souza, in the Biochemistry curricular component. I chose the food theme because it offers a broad approach to chemical concepts. 40 students from the first module of the Technical Course in Pharmacy at ETEC Francisco Garcia have participated in the activities. The theme of food was important for providing knowledge of the chemical processes involved in the preparation, conservation and deterioration of food, enabling students to make critical and autonomous choices regarding what they consume and about their health. The students were instructed to record the activities carried out in the logbooks. The logbooks were collected for analysis and discussion of the results. Data were analyzed through reports, questionnaires, graphs and tables. The data analysis has shown a change in attitude and learning, and also an improvement in the autonomy of students who were more confident when seeking the information, they needed. The research has demonstrated the development of scientific knowledge and critical thinking in students, making them become more critical and reflective citizens.
Study of biomolecules in food: a possibility for learning organic functions
Keywords: Biomoléculas; Alimentos; Contextualização; Química; Biochemistry; Foods; Contextualization; Chemical; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO